2021
DOI: 10.1002/mp.14727
|View full text |Cite
|
Sign up to set email alerts
|

High resolution small‐scale inorganic scintillator detector: HDR brachytherapy application

Abstract: Purpose: Brachytherapy (BT) deals with high gradient internal dose irradiation made up of a complex system where the source is placed nearby the tumor to destroy cancerous cells. A primary concern of clinical safety in BT is quality assurance to ensure the best matches between the delivered and prescribed doses targeting small volume tumors and sparing surrounding healthy tissues. Hence, the purpose of this study is to evaluate the performance of a point size inorganic scintillator detector (ISD) in terms of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…This calibration distance is larger than the separation of the detector from the source in the patient measurements, ensuring that the SNR in these cases is much higher than the values reported in the SNR section. Although Debnath et al reported a higher SNR for their inorganic scintillator detector, the energy dependence of this type of detector is an important disadvantage in comparison with the PSD in the present study [ 27 ].…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…This calibration distance is larger than the separation of the detector from the source in the patient measurements, ensuring that the SNR in these cases is much higher than the values reported in the SNR section. Although Debnath et al reported a higher SNR for their inorganic scintillator detector, the energy dependence of this type of detector is an important disadvantage in comparison with the PSD in the present study [ 27 ].…”
Section: Discussionmentioning
confidence: 62%
“…Despite these differences of the individual dwell positions, it is important to note that the maximum total treatment time difference was below 0.3% in all the patients measured. The average accuracy reported by Debnath et al was 0.09%, while the percent deviation of all the measured dwell times in this work was below 0.01% [ 27 ].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…That is, when the ratios ofD det and D wat are taken at a given position (r 0 , θ), the source anisotropy effect does not cancel out. As a result, the absorbed-dose energy dependence correction factor can have multiple values at the same radial distance r. The findings demonstrate that a single absorbed-dose energy correction function is not sufficient for high-Z detectors although it is adopted in some experimental studies (e.g., Ruiz-Arrebola et al 2020, Debnath et al 2021).…”
Section: Inorganic Scintillators For In Vivo Dosimetry In 192 Ir Brachytherapymentioning
confidence: 95%
“…(Kertzscher and Beddar 2019, Linares Rosales et al 2020b, Debnath et al 2021, Jørgensen et al 2021a.…”
mentioning
confidence: 99%